Letter - Crook, J.
034-0008-001 COMMUNICATIONS—WRITE ON SEPARATE SHEETS FOR EACH SUBJECT AMALGAMATED UNION OF BUILDING TRADE WORKERS OF GREAT BRITAIN AND IRELAND Approved Society No. 257. Telegrams: "Buildcres, Clapcom, London." Telephone: Macaulay 2442 (3 lines) Camberwell (1) Branch Secretary's Address 82 Faraday St S.E.17 Date 31 Aug 1942 Our Ref. Your Ref. The Rt Hon Sir Walter Citrine Dear Sir The resolution outlined below was carried by the members of the above branch of this Union at our last meeting and which I was directed to forward to you for your attention. Resolution "This branch calls upon the Trades Union Congress to do all within its power to urge the Government to take steps, together with other Governments concerned, for the immediate release of members of the International Brigade who fought in Spain, 1500 of which have for four years been held prisoner under indescribable conditions in France, Spain and North Africa". Yours Fraternally J. Crook Bch Sec [Branch Secretary] 292/946/34/8